Adapting Language Curriculum for Diverse Learners: Strategy for Inclusive Education - Edor, John; Odey, Elizabeth Akpanke; Nwosu, Enyioma E.; Ncha, Gabriel Bubu; Edem, Essien Udoaka; Ekpenyon, Ekpenyong Obo; Etta, Robert Bikom; Emeng, Gideon Imoke; Aboh, James Ajang; Asuquo, Offiong Offiong; Ozumba, Lily Nnenna; Edet, Louis Ajom (Forum for Linguistic Studies, 2025)
In an era of globalization, classrooms are becoming increasingly diverse, necessitating the adaptation of language curricula to meet the varied needs of learners. This paper investigates effective strategies for designing inclusive language education that acknowledges and leverages students' diverse linguistic and cultural backgrounds. Through a comprehensive literature review, qualitative interviews with educators and quantitative surveys using ex-post-facto or causal comparative research design. The target population consisted of selected primary schools in Calabar Municipality. The estimated primary school population was 108,074 based on the school register. It is assumed that all these members of the population are in one way or another involved in both the diverse language learning process and also not involved vis-à-vis. The sample consisted of 506 individuals drawn from the study population. Stratified random sampling techniques were used in selecting the subjects Questionnaire items was deployed using the theoretical frameworks such as constructivism, culturally responsive teaching, universal design for learning UDL, Socio-cultural theory, differentiated instruction, critical pedagogy, and second language acquisition SLA were adapted as a paradigm to justify the results of the findings and it provided a comprehensive foundation for adapting language curricula for diverse learners. This study identifies key practices that enhance engagement and learning outcomes. Findings suggest that curricula that incorporate culturally relevant materials, differentiated instruction, and collaborative learning environments significantly benefit diverse learners. The findings underscore the necessity of flexible curricula that accommodate different learning styles and abilities, ultimately enhancing language acquisition and fostering an inclusive atmosphere. The paper concludes with actionable recommendations for educators and policymakers aimed at fostering inclusive language education.